TRPV1 Receptor-Mediated Hypoglycemic Mechanism of Capsaicin in Streptozotocin-Induced Diabetic Rats - Zhang, Shiqi; Tang, Lanlan; Xu, Fanshu; Hui, Yonghai; Lu, Hongjia; Liu, Xiong (Frontiers in Nutrition, 2021)
Our previous research showed that capsaicin exhibits hypoglycemic effects by activating the transient receptor potential vanilloid 1 (TRPV1) channel in diabetic rats. Interestingly, capsiate was also able to activate the TRPV1 channel, but with a nonsignificant hypoglycemic effect. This study aimed to investigate the effect of capsaicin on the glycometabolism of streptozotocin (STZ)-induced diabetic rats by blocking the TRPV1 channel. After a four-week capsaicin treatment (6 mg/kg•bw), the serum insulin level of STZ-induced diabetic rats increased from 15.2 to 22.1 mIU/L, the content of hepatic glycogen and muscle glycogen increased by 81.2% and 20.2%, respectively, and the blood glucose level decreased significantly from 19.3 to 14.7 mmol/L. When the TRPV1 channel was blocked, capsaicin lost the above-mentioned effects, and the hypoglycemic effect was no longer significant. It was concluded that a combined up-regulation of both TRPV1 receptors and pancreatic duodenal homeobox-1 (PDX-1) led to the hypoglycemic effect of capsaicin, which partially explains our previous observation: capsiate activating TRPV1 without showing a significant hypoglycemic effect was due to the lack of a significant up-regulation of PDX-1. Based on the experimental results, we speculated that two signaling pathways (TRPV1-(PDX1)-(GLUT2/GK) and TRPV1-(PDX-1)-(IRS1/2)) exist in the pancreas of STZ-induced diabetic rats.